1984
DOI: 10.1021/ma00138a038
|View full text |Cite
|
Sign up to set email alerts
|

Slow-mode diffusion of poly(vinylpyrrolidone) in the semidilute regime

Abstract: Theseworkers claim that the complex of poly(acrylic acid) and polyethylene imine) can be transformed into a ladder-like structure of condensed nine-membered rings. See also: Ka-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

1988
1988
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 3 publications
1
22
0
2
Order By: Relevance
“…This slow relaxation time has been predicted and observed to be q -independent. Good solvent, semidilute systems are not expected to display slow mode behavior, and this has been found to be generally true for hydrocarbon systems. , However, various aqueous, good solvent systems have been found to display slow mode behavior in the semidilute region. , To our knowledge, the physical cause of this anomalous behavior has not been explained. In this paper we present some experimental results on PVP in water and denatured water in an attempt to elucidate the origin of this slow mode.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…This slow relaxation time has been predicted and observed to be q -independent. Good solvent, semidilute systems are not expected to display slow mode behavior, and this has been found to be generally true for hydrocarbon systems. , However, various aqueous, good solvent systems have been found to display slow mode behavior in the semidilute region. , To our knowledge, the physical cause of this anomalous behavior has not been explained. In this paper we present some experimental results on PVP in water and denatured water in an attempt to elucidate the origin of this slow mode.…”
Section: Introductionmentioning
confidence: 93%
“…PVP has a wide variety of commercial applications, finding use in the medical, food, and pharmaceutical industries for such diverse uses as a blood plasma substitute, binding agent for drug delivery, and food thickener. , Because of its many uses and its structural similarity to biopolymers, PVP has been extensively studied through nearly every technique used in the characterization of macromolecules including viscometry, osmometry, NMR, and light scattering. Past light scattering experiments have been somewhat limited. The molecular weight scaling behavior has been not quantified for the dilute concentration regime, nor has there been a complete investigation of the slow mode, discovered in the autocorrelation function in the semidilute region . Of particular interest is the origin of this slow mode.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is well known for many polymers. In particular, for PVP, in a study of its solutions in a wide range of concentrations, it was shown that, whereas in solutions with a low concentration a single mode is observed on analogous dependences, with increase in the polymer concentration a second (slow) mode begins to appear on the dependences, refl ecting the formation of associates of macromolecules in the solution [14].…”
Section: Experimental Correlation Functions Of Dynamic Lightmentioning
confidence: 99%
“…Αν και η ποσοτική ανάλυση των πειραματικών δεδομένων για την "αργή" διεργασία χαλάρωσης αποδείχθηκε προβληματική, ποιοτικά συμπε ράσματα μπορούν να εξαχθούν τα οποία σε συνδυασμό με δεδομένα της βιβλιογραφίας μπορούν να οδηγήσουν στον καθορισμό της φύσης και προέ λευσης της συγκεκριμένης διεργασίας. Κατ' αρχάς πέρα από τις διακυμάνσεις πυκνότητας, συγκέντρωσης και προσανατολισμού, έχει παρατηρηθεί η ύπαρξη μιας αργής διεργασίας χαλάρωσης σε διαλύματα υψηλών συγκεν τρώσεων πολυμερικών συστημάτων [117][118][119][120] καθώς και σε περιπτώσεις καθαρών [121] και δυαδικών μιγμάτων απλών μη πολυμερικών υγρών [122]. Στις παραπάνω μελέτες θεωρήθηκε ότι οι αργές κινήσεις συσσωματωμάτων (clusters) είναι υπεύθυνες για την αργή διεργασία χαλάρωσης καθώς και για την περίσσεια σκεδαζόμενης έντασης πέρα από αυτή που προβλέπεται από τη θεωρία (βλέπε εξ.…”
Section: J Fq C T>t Cunclassified
“…Τα παραπάνω χαρακτηριστικά της δυναμικής συμπεριφοράς της "αργής" διεργασίας έρχονται σε συμφωνία με αυτά που παρατηρήθηκαν σε μίγματα πολυμερικής και μη φύσης, και αποδόθηκαν στην ύπαρξη μεγάλων εκτεταμένων δομών (τύπου clusters) που διαχέονται αργά μέσα στον κύριο όγκο του υγρού [117][118][119][120][121][122]. Είναι αξιοσημείωτο ότι στη συστηματική μελέτη PCS των δυαδικών μιγμάτων Van der Waals υγρών (o-terphenyl (ΟΤΡ) -BCDE, OTP-BKDE) των Gerhartz et al προσδιορίσθηκε μια μέση διάμετρος clusters ~ 1000 Α, η οποία θεωρήθηκε υπεύθυνη για την εξάρτηση της σκεδαζόμενης έντασης από τις γωνίες θ. Λαμβάνοντας υπόψη την ιδιόμορφη δομή του ZnCI 2 (βλέπε Κεφ.…”
Section: J Fq C T>t Cunclassified